Crystal Structures of the Catalytic Domain of Arabidopsis thaliana Starch Synthase IV, of Granule Bound Starch Synthase From CLg1 and of Granule Bound Starch Synthase I of Cyanophora paradoxa Illustrate Substrate Recognition in Starch Synthases - Nielsen, Morten M.; Ruzanski, Christian; Krucewicz, Katarzyna; Striebeck, Alexander; Cenci, Ugo; Ball, Steven G.; Palcic, Monica M.; Cuesta-Seijo, Jose A. (Frontiers in Plant Science, 2018)
Starch synthases are responsible for depositing the majority of glucoses in starch. Structural knowledge on these enzymes that is available from the crystal structures of rice granule bound starch synthase (GBSS) and barley starch synthase I provides incomplete information on substrate binding and active site architecture. Here we report the crystal structures of the catalytic domains of SSIV from Arabidopsis thaliana, of GBSS from the cyanobacterium CLg1 and GBSSI from the glaucophyte Cyanophora paradoxa, with all three bound to ADP and the inhibitor acarbose. The SSIV structure illustrates in detail the modes of binding for both donor and acceptor in a plant starch synthase. CLg1GBSS contains, in the same crystal structure, examples of molecules with and without bound acceptor, which illustrates the conformational changes induced upon acceptor binding that presumably precede catalytic activity. With structures available from several isoforms of plant and non-plant starch synthases, as well as the closely related bacterial glycogen synthases, we analyze, at the structural level, the common elements that define a starch synthase, the elements that are necessary for substrate binding and singularities of the GBSS family that could underlie its processivity. While the phylogeny of the SSIII/IV/V has been recently discussed, we now further report the detailed evolutionary history of the GBSS/SSI/SSII type of starch synthases enlightening the origin of the GBSS enzymes used in our structural analysis.